Unravelling the role of secretory Immnuoglobulin-A in COVID-19: a multicentre study in nursing homes during the first wave - Rafael Bielza; Patricia Pérez; Nuria García; Laura Ballesteros-Sanabria; Rosa María Martínez; Azam Ghazi; Clara Hernando; María Victoria Rodríguez; Israel J. Thuissard; Cristina Andreu-Vázquez; José Manuel Bautista (BMC Geriatrics, 2024)
Abstract Background The function of mucosal secretory IgA (SIgA) seems to be paramount in the immune response against SARS-CoV-2 however, there are few studies addressing this issue specifically in the institutionalized older population. This study aims to determine the levels of secretory IgA against the S1 domain of the SARS-CoV-2 spike (SIgA-S1) in older people living in nursing homes (NH) and to investigate the differences in baseline characteristics, severity of COVID-19, duration of symptoms, 30-day mortality, and reinfection according to the levels of SIgA-S1. Methods In this multicentre longitudinal study, conducted in two NHs attended in coordination with a hospital-based Geriatric team, 305 residents (87.3 years, 74.4% female) were included. A massive collection of nasopharyngeal samples was carried out after the first wave of COVID-19 in May 2020 and an ELISA analysis of SIgA-S1 was performed on frozen samples in May 2023. Values of SIgA-S1 ≥ 57.6 U/mL (“cut-off point”) were considered “induced”. Resident medical records were reviewed to assess symptoms, comprehensive geriatric assessment (CGA), reinfection, and overall 30-day mortality. Results At the time of sample collection, 274 residents (89.8%) exhibited “induced” SIgA-S1 levels (≥ 57.6 U/mL), 46 (15.1%) tested positive for PCR SARS-CoV-2, and 170 (57%) had experienced COVID-19 symptoms. “Induced” SIgA-S1 patients were more likely to be symptomatic (60.3% vs. 29%; p < 0.001) and exhibited upper respiratory tract symptoms more frequently (25.1% vs. 6.5%; p = 0.020) compared to “non-induced” patients. Patients with severe disease and duration of symptoms > 10 days had higher levels of SIgA-S1 than those with mild disease (252 vs.192.6 U/mL; p = 0.012) or duration ≤ 10 days (270.5 vs. 208.1 U/mL; p = 0.043), respectively. No significant differences were observed in age, sex, CGA, duration of symptoms, disease severity, overall 30-day-mortality, or reinfection between “induced” and “non-induced” residents. Conclusions Levels of SIgA-S1 are associated with the duration and type of COVID-19 symptoms, along with the severity of infection. While these findings shed light on the knowledge of SIgA-S1, further interdisciplinary studies are warranted to better understand the immune response to SARS-CoV-2 infection.